Education and health knowledge: Evidence from UK compulsory schooling reform. (February 2015) - Johnston, David W.; Lordan, Grace; Shields, Michael A.; Suziedelyte, Agne
Abstract: We investigate if there is a causal link between education and health knowledge using data from the 1984/85 and 1991/92 waves of the UK Health and Lifestyle Survey (HALS). Uniquely, the survey asks respondents what they think are the main causes of ten common health conditions, and we compare these answers to those given by medical professionals to form an index of health knowledge. For causal identification we use increases in the UK minimum school leaving age in 1947 (from 14 to 15) and 1972 (from 15 to 16) to provide exogenous variation in education. These reforms predominantly induced adolescents who would have left school to stay for one additionally mandated year. OLS estimates suggest that education significantly increases health knowledge, with a one-year increase in schooling increasing the health knowledge index by 15% of a standard deviation. In contrast, estimates from instrumental-variable models show that increased schooling due to the education reforms did not significantly affect health knowledge. This main result is robust to numerous specification tests and alternative formulations of the health knowledge index. Further research is required to determine whether there is also no causal link between higher levels of education – such as post-school qualifications – and health knowledge. Highlights: We investigate the causal link between education and health knowledge. For casual identification we use increases in the UK minimum school leaving age in 1947 and 1972. OLS estimates suggest that education significantly increases health knowledge. Instrumental-variable estimates show that increased schooling did not significantly affect health knowledge.